Enduring Indigeneity: Community Consultation as a Process for Indigenizing Curriculum at a College in Ontario - Di Iulio, Camille C. (Scholarship@Western, 2022)
In 2015, the Truth and Reconciliation Commission (TRC) released its report which included 94 Calls to Action to address the legacy impacts of the Indian Residential School System in Canada. With education at the forefront of reconciliation, Call to Action #62 calls on post-secondary educators to integrate First Nations, Métis and Inuit content into their curriculum, to Indigenize teaching and learning within an education system built on Eurocolonial worldviews. A post-secondary institution located in southern Ontario (referred to by the pseudonym SCAAT) is making decolonization an institutional priority, especially as it is aligned with their Equity, Diversity and Inclusion (EDI) initiatives. Therefore, this Organizational Improvement Plan (OIP) aims to address the deficit of Indigenous worldviews represented across curriculum within the Faculty of Arts (FOA) at SCAAT through a process of Indigenization. Change agents will implement a consultation process with members of the local First Nation on whose traditional territory the college resides, so that curriculum reform for Indigenous education is informed by place-based stories, histories, knowledge and perspective; this underscores the objective of Indigenization. The author of this OIP identifies as Anishinaabe and the change is approached in an Indigenous wholistic framework, where it is pertinent that the writing privileges Indigenous perspectives, epistemologies, and methodologies. Through meaningful Indigenization, the FOA demonstrates a commitment to the authentic resurgence of Indigenous identity across curriculum offerings which will contribute to mutually respectful Indigenous-settler relations in support of reconciliation.